Carboxymethyl chitosan functionalization of Bi2S3 quantum dots: Towards eco-friendly fluorescent core-shell nanoprobes. (1st August 2016) - Mansur, Alexandra A.P.; Ramanery, Fábio P.; Oliveira, Luiz C.; Mansur, Herman S.
Graphical abstract: Polysaccharides: From the shells of crustaceans to core-shell nanostructures . Schematic Representation of the core-shell nanohybrid structures composed of carboxymethyl chitosan-Bi2 S3 quantum dots. Highlights: Bi2 S3 nanocrystals functionalized with O- carboxymethyl chitosan (OCMC) were prepared. Nanohybrids with OCMC using a single-step eco-friendly water process were developed. Novel stable colloidal core-shell nanostructures based on Bi2 S3 /OCMC were produced. OCMC acted as a pH-depend functional ligands affecting the Bi2 S3 nanocrystals formed. Core-shell nanostructures based on Bi2 S3 /OCMC were luminescent in the visible light. Abstract: Designed bioengineered nanocomposites are emerging as a novel class of hybrid materials composed of natural aminopolysaccharides and inorganic semiconductors for biomedical and environmental applications. In this study, it is reported for the first time the synthesis and characterization of water-soluble Bi2 S3 quantum dots (QDs) functionalized with O- carboxymethyl chitosan ( O -CMC) as capping ligands. UV–vis spectroscopy, transmission electron microscopy, dynamic light scattering, zeta potential, and photoluminescence spectroscopy were used to characterize these nanohybrids. The results proved the hypothesis that O -CMC acted as a pH-dependent multi-functional ligand by altering the mechanisms of nucleation, growth and stabilization of water-soluble colloidal Bi2 S3 nanocrystals under acidic, physiological and alkaline conditions, using an eco-friendly aqueous process at room temperature. Moreover, the O -CMC capping ligand and the relative molar ratios of the precursors in solution effectively controlled the diameters of the Bi2 S3 QDs, which ranged from 2.8 to 12.8 nm, and that exhibited luminescent properties in visible light.